Assessing the Determinants of Capital Structure Before and During Indonesia's Infrastructure Plans: Examining Indonesia's IDX-Listed Firms Between 2010-2014 and 2015-2019 - Setyawan, Dede; Santoso, Felicia (iBuss Management, 2021)
Indonesia is putting an ambitious infrastructure plan into motion, but the plan is widely reported to contribute towards the rising level of debt-to-equity ratio by Indonesia’s state-owned enterprises (SOEs). In order to clarify the factors that influence SOEs’ increasing leverage, this study compares the determinants of capital structure of Indonesia’s IDX-listed firms before (2010-2014) and during (2015-2019) Indonesia’s infrastructure plan, dividing the samples into two time periods accordingly. Observations from 12 SOEs and 210 non-SOEs listed in IDX between 2010-2019 are analyzed using paired t-test as well as multiple linear regression, which examines determinants of capital structure in the form of state ownership, profitability, firm size, tangibility, growth, liquidity, debt tax shield, and firm risk. As a result, the existence of statistically significant increase in SOE leverage from 2010-2014 to 2015-2019 is proven. Profitability, firm size, tangibility, liquidity, and firm risk are found to be consistently significant determinants during both periods. Growth is also a consistently significant determinant if extreme outliers are excluded, while debt tax shield is not found to be significant. State ownership is significant between 2010-2014 but not between 2015-2019, implying that SOEs do not have significantly higher leverage than non-SOEs during Indonesia’s infrastructure plans.Keywords:State Ownership, Leverage, Growth, Firm Risk, Profitability, Firm Size, Tangibility, Liquidity, Infrastructure Plan, Debt-to-Equity, Expansionary Fiscal Policy.